2021
DOI: 10.12659/msm.932996
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Long Non-Coding RNA (lncRNA) SNHG5 in Patients with Refractory Diabetic Macular Edema and Its Regulatory Mechanism

Abstract: Background The aim of this study was to assess use of lncRNAs as biomarkers in serum and aqueous humor of patients with diabetic macular edema (DME). Material/Methods Optical coherence tomography and fundus photography were used to analyze the retinal features of the patients. RT-qPCR was used to analyze the differential expression of lncRNA snhg5 in patients who have idiopathic macular hole (MH), DME, or refractory DME. The relationship between SNHG5 and the clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…The expression of SNHG5 decreased in both atrial uid and plasma in diabetic macular edema patients. The nding presented a negative correlation with some clinical indicators, including disease duration, body mass index, and fasting blood glucose levels [32] . MALAT1 could protect the retina from oxidative damage via regulating the Keap1-Nrf2 axis [33] .…”
Section: Discussionmentioning
confidence: 91%
“…The expression of SNHG5 decreased in both atrial uid and plasma in diabetic macular edema patients. The nding presented a negative correlation with some clinical indicators, including disease duration, body mass index, and fasting blood glucose levels [32] . MALAT1 could protect the retina from oxidative damage via regulating the Keap1-Nrf2 axis [33] .…”
Section: Discussionmentioning
confidence: 91%
“…This SNHG is located on chromosome 6q14.3 and hosts SNORD50A and SNORD50B [ 183 ]. The levels of SNHG5 are impaired in the atrial fluid and blood of DME subjects, as well as in patients with refractory DME vs. those with idiopathic macular hole [ 191 ]. Moreover, SNHG5 expression in plasma and aqueous humor negatively correlates with the duration of disease and body mass index [ 191 ].…”
Section: The Deregulation Of Small Nucleolar Rna Host Genes In Diabet...mentioning
confidence: 99%
“…The levels of SNHG5 are impaired in the atrial fluid and blood of DME subjects, as well as in patients with refractory DME vs. those with idiopathic macular hole [ 191 ]. Moreover, SNHG5 expression in plasma and aqueous humor negatively correlates with the duration of disease and body mass index [ 191 ]. Moreover, HRMECs exposed to HG display reduced expression of SNHG5 [ 191 ].…”
Section: The Deregulation Of Small Nucleolar Rna Host Genes In Diabet...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, higher levels of LncRNA LIPCAR are associated with a higher risk of cardiovascular mortality ( 131 ), and LncRNA NONHSAT112178 can be a possible predictive biomarkers for coronary artery disease ( 132 ), Lnc HOTAIR is highly expressed in saliva samples of oral squamous cells from carcinoma patients, making it a strong candidate for metastatic oral cancer diagnosis ( 133 ), and Lnc MALAT1 is elevated in plasma and urine of prostate cancer patients ( 134 ). In diabetic retinopathy, Lnc HOTAIR and Lnc MALAT1 have shown some discrimination between patients with nonproliferative and proliferative retinopathy ( 135 ) and plasma and aqueous humor levels of LncRNA small nucleolar RNA host gene 5 are negatively correlated with the development of diabetic macular edema ( 136 ). A recent study has shown a strong correlation between the differential expressions of nine LncRNAs including Lnc ANRIL , Lnc HOTAIR and Lnc MIAT , in the vitreous and serum samples of patients with or without diabetic retinopathy; these promising results suggest the possible use of serum LncRNAs as a potential biomarker of diabetic retinopathy, however, their validation in a larger cohort is needed ( 137 ).…”
Section: Long Noncoding Rnas As Biomarkers and Therapeutic Optionsmentioning
confidence: 99%